Prophet, pastor, and patriarch: the rhetorical leadership of Alexander Campbell - Verkruyse, Peter (University of Alabama Press, 2005)
Alexander Campell's Restoration Movement -- Alexander Campbell's philosophy of rhetoric -- The "Sermon on the law" and the art of constitutive rhetoric -- Ridicule and residue : the prophetic tone of the Christian Baptist -- Managing ideological difference : classification, transcendence and the letter from Lunenburg -- "The missionary cause" : epideictic narrative and rhetorical vision